St. Augustine - Topping, Ryan N. S. (Continuum library of educational thought, 2010)
Intellectual biography -- Approaching Augustine -- Critical exposition -- The aims of education -- The art of the teacher -- The matter of learning -- The limits of instruction -- Philosophical reception and relevance -- Augustine and some philosophers of education -- Augustine and the defence of liberal education